Perilaku Produsen Islam - Sri Laksmi Pardanawati (ITB AAS INDONESIA Surakarta, 2015)
Production is matarantai consumption, which provide goods and services that are the need of consumers, producers as consumers, aiming to obtain the maximum maslahah through its activities. So the producers in the economic perspective of Islam is not a hunter but the hunter mashlahah maximum profit. Expression mashlahah in production activities is a boon and a blessing, so produsen will determine the combination of blessings and benefits that provide maximum mashlahah. Therefore, the aim of manufacturers is not just profits, then consideration also not just the things that are resources that have a technical connection with the output, but also consideration of the content of blessing (nontechnical) that exist on the resources and output Keywords : Behavior, Producer